Note on Rondibilis similis (Coleoptera: Cerambycidae: Lamiinae) - Huang, Gui-Qiang; Vitali, Francesco (Zootaxa, 2015)
Eryssamena was erected by Bates (1884) based on three species E. saperdina, E. acuta and E. spinidorsis, which Breuning (1977) recognised to be the same species: Eryssamena saperdina Bates, 1884. Although Eryssamena had been accepted as an independent genus for a long time, Kusama & Takakuwa (1984) and Hashimoto (2008) considered it as a subgenus of Rondibilis Thomson, 1857. Holzschuh (2003) treated Eryssamena as a synonym of the nominotypical subgenus. Ohbayashi & Niisato (2007) and Löbl & Smetana (2010) considered Eryssamena as a synonym of Rondibilis. We have found that the Laotian Eryssamena similis Breuning, 1965 is a secondary homonym of Rondibilis similis Gahan, 1907. According to the Art 57.3.1 of ICZN (International Commission on Zoological Nomenclature, 1999), we hereby propose the replacement name Rondibilis subquadrinotata nom. n. for Eryssamena similis Breuning, 1965. The lectotype and a paralectotype are designated for Rondibilis similis Gahan, 1907.